A Comparative Analysis of Factors Influencing the Sustainability of the Abia State Health Insurance Agency: Insights From Rural-Urban Abia State - Ukweh H. Ikechukwu FMCPH; Ukweh N. Ofonime FWACS; Iya-Benson N. Joy FWACP; Oku O. Afiong FWACP; Ewelike Uchenna PhD; Iziga-Eruchalu G. Chiesonu MSc (SAGE Publishing, 2024)
The goal of the Abia State Health Insurance Agency (ABSHIA) has been to increase coverage since its implementation. However, the sustainability of the scheme is crucial to continue providing affordable healthcare in the State. This study aimed to identify and compare factors that influence the sustainability of ABSHIA in rural-urban areas of Abia State. The study used a mixed-method cross-sectional design that involved collecting data through a questionnaire on enrollment, satisfaction, and willingness to renew membership. Key informant interviews and focus group discussions were also conducted to obtain qualitative data from healthcare providers and ward development committees. The collected data were analyzed using appropriate statistical tests. The results showed a higher enrollment in rural areas compared to urban areas, with no significant difference in satisfaction and willingness to renew membership between the 2 locations. The study also identified factors that positively influenced willingness to renew membership, but it was found that traveling a distance of 15 min or more decreased willingness to renew membership in urban Abia. Furthermore, poor health status was found to have a low influence on willingness to renew membership in rural Abia. Among other barriers to renewal, poor quality of care and, nonpayment of health workers' capitation was identified as significant factors. It is crucial to prioritize the sustainability of ABSHIA to achieve the sustainable development goal of health for all in the State.